Outcomes of Laparoscopic Gastric Resection for Submucosal Tumors at Difficult Locations: A Prospective Cohort Study - Rakchob, Teerawut; Seehawong, Umaporn; Moonwiriyakit, Pienlert (The Thai Journal of Surgery, 2025)
Background: The most common type of submucosal tumor in the stomach is gastrointestinal stromal tumors (GISTs). The standard treatment involves surgical removal with clear margins and without tumor rupture. Current treatment increasingly supports laparoscopic surgery, particularly for tumors located in difficult-to-access locations. This study compares laparoscopic surgery (LapS) and open surgery (OpenS) for gastric submucosal tumors located in such areas. Objective: This study aimed to evaluate survival analysis and assess surgical outcomes associated with both techniques. Materials and Methods: A prospective cohort study was conducted between August 2021 and August 2024 at Buri Ram Hospital. evaluating patients with gastric submucosal tumors through esophagogastroduodenoscopy (EGD). Tumors were located in challenging stomach areas, including the EGJ, cardia, lesser curvature, posterior wall, and pyloric ring of the antrum. The data were analyzed, and a p-value of less than 0.05 was considered statistically significant. Results: The study included 37 patients, 19 in the LapS group and 18 in the OpenS group. There were no significant differences in age, sex, or BMI between the two groups. However, tumors at the lesser curvature were more prevalent in the OpenS group compared to the LapS group (p = 0.044). Partial gastric resection was performed more frequently in the LapS group (p = 0.004). The LapS group demonstrated better postoperative outcomes, including reduced blood loss, earlier initiation of feeding, earlier passage of flatus, and a shorter hospital stay. The median follow-up time was 19 months. The survival rate in the LapS group was 89.5%, compared to 77.8% in the OpenS group. No significant difference in survival analysis between the two groups (HR 0.54, 95% CI: 0.09-2.98, p = 0.482). Conclusion: For submucosal tumors located in challenging areas of the stomach, laparoscopic surgery offers advantages in terms of minimally invasive approaches and oncologic outcomes compared to open surgery.